2016
DOI: 10.1016/j.neuron.2016.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Imaging Reveals Properties of Glutamate-Induced Arc/Arg 3.1 Translation in Neuronal Dendrites

Abstract: Summary The immediate early gene Arc (also Arg3.1) produces rapid changes in synaptic properties that are linked to de novo translation. Here we develop a novel translation reporter that exploits the rapid maturation and “flash” kinetics of Gaussia luciferase (Gluc) to visualize Arc translation. Following glutamate stimulation, discrete Arc-Gluc bioluminescent flashes representing sites of de novo translation are detected within 15 s at distributed sites in dendrites, but not spines. Flashes are episodic, last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 83 publications
(118 reference statements)
0
55
1
Order By: Relevance
“…These findings suggest that dendritically localized synaptic plasticity-related mRNAs like Arc are markers of where synaptic plasticity is occurring and that BLA activation is a regulator of when it occurs. Na et al (2016) recently found that glutamate induced rapid translation of ARC in hippocampal dendrites and that reactivation of stalled polyribosomes mediated this effect. Figure 3 provides a schematic diagram for how the BLA influences ARC expression in regions, such as the hippocampus, important for processing declarative memory information.…”
Section: A Basolateral Amygdala Influence On Expression Of Plasticitmentioning
confidence: 99%
“…These findings suggest that dendritically localized synaptic plasticity-related mRNAs like Arc are markers of where synaptic plasticity is occurring and that BLA activation is a regulator of when it occurs. Na et al (2016) recently found that glutamate induced rapid translation of ARC in hippocampal dendrites and that reactivation of stalled polyribosomes mediated this effect. Figure 3 provides a schematic diagram for how the BLA influences ARC expression in regions, such as the hippocampus, important for processing declarative memory information.…”
Section: A Basolateral Amygdala Influence On Expression Of Plasticitmentioning
confidence: 99%
“…Alternatively, synthetic reporters harboring the rapidly maturing Gaussia luciferase (Gluc) can be used to monitor protein synthesis in real time with sub-cellular resolution [17]. Gluc requires only the substrate coelenterazine (CTZ), and no other cofactors ( e.g.…”
Section: Luminescent Labeling Of Newly Synthesized Proteinmentioning
confidence: 99%
“…In general, these techniques do rely on the delivery of chemical reagents, and in many cases require fixation before measurement as well. Nonetheless, they can reveal the variations in translatability among cell populations [7,12,13] and animal tissue [12], and of local translation [9] such as in the dendrites of neurons [10,1417]. …”
Section: Luminescent Labeling Of Newly Synthesized Proteinmentioning
confidence: 99%
“…Hebbian plasticity paradigms triggers homeostatic scaling in neurons as a compensatory mechanism (Vitureira & Goda, 2013); these two opposing forms of plasticity must involve a combination of overlapping and distinct molecular players. Our data demonstrates the requirement of a rapamycin-sensitive, MOV10 degradation-dependent Arc translation in homeostatic scaling that is distinct from the rapamycin-insensitive dendritic translation of Arc ocurring during Hebbian plasticity (Na et al, 2016). We speculate that homeostatic and Hebbian plasticity engages distinct signalling pathways that converge at miRISC remodelling.…”
Section: Degradative Control Of Mirisc Remodelling Underlies Homeostamentioning
confidence: 72%